Synthesis and Characterization of Mononuclear and Binuclear Complexes of Ni(II) and Cu(II) derived from Aromatic Hydrazones - MANDAL, R.S.; MISHRA, LALITA (Asian Journal of Chemistry, 2010)
In the present work, the synthesis and characterization of mononuclear and binuclear complexes of Ni(II) and Cu(II) derived from aromatic hydrazones is described.